1991
DOI: 10.7326/0003-4819-115-10-787
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Serious Gastrointestinal Complications Related to Use of Nonsteroidal Anti-inflammatory Drugs

Abstract: Users of NSAIDs are at approximately three times greater relative risk for developing serious adverse gastrointestinal events than are nonusers. Additional risk factors include age greater than 60 years, previous history of gastrointestinal events, and concomitant corticosteroid use. Another possible risk factor is the first 3 months of NSAID therapy. The risk for serious gastrointestinal events appears to be equal among men and women. These data represent summary statistics from 16 studies and cannot be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
502
0
19

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,137 publications
(531 citation statements)
references
References 46 publications
10
502
0
19
Order By: Relevance
“…The list of characteristics was based on literature about the methods of epidemiologic studies in general and on previous meta-analyses on anti-in¯ammatory drugs and UGIC [6,7,59]. Data from articles was abstracted in duplicate and entered into a database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of characteristics was based on literature about the methods of epidemiologic studies in general and on previous meta-analyses on anti-in¯ammatory drugs and UGIC [6,7,59]. Data from articles was abstracted in duplicate and entered into a database.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the general population, early observational studies have reported risks of upper gastrointestinal complications (UGIC) from 1 to 10 times higher among aspirin users, with an estimated pooled relative risk between 2 and 3 [6,8], Nonetheless, the fact that aspirin is widely available over-the-counter without prescription complicates the assessment of its effects in observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have attempted to provide estimates of the risks of upper GI complications of NSAIDs (7)(8)(9)(10)(11). With 1 exception, these reviews have focussed on perforations, ulcers, or bleeds.…”
Section: Introductionmentioning
confidence: 99%
“…All drug categories were mentioned in all settings; NSAIDs were mentioned most frequently at 51.2% of drug visits for arthritis (data not shown). Little data exist to judge the appropriateness of this rate of NSAID orders, but the documented adverse health effects (31)(32)(33) and economic (34) consequences of NSAID use support other studies (35,36) suggesting this is potentially a large medical and public health problem. We could not assess the effect of the availability of COX-2 inhibitors, introduced after 1997, on the rate of NSAID orders during arthritis visits; this is an important area for future research.…”
mentioning
confidence: 99%